Reactivation and Flare of Chronic Hepatitis B: Natural History, Diagnosis, Therapy and Prevention - Suharjo Broto Cahyono; Neneng Rasari Neneng Rasari; Putut Bayupurnama; Sutanto Maduseno; Siti Nurdjanah (Acta Interna The Journal of Internal Medicine, 2014)
ABSTRACTAlmost 30% of the world population has been exposed to hepatitis B virus (HBV) and 400 millionof these are chronically infected. 20–30% of HBsAg carriers may develop reactivation or fl are (acuteexacerbation) of chronic hepatitis B with elevation of biochemical levels, high serum HBV DNA level with orwithout sero-coversion to HBeAg. In countries with intermediate or high endemicity for HBV, compoundedin use cytotoxic or immunosuppressive therapy for the treatment of a wide variety of clinical disease,reactivation or fl are may be the fi rst presentation of HBV infection. Sometime it is diffi cult to differentiatebetween acute hepatitis B and reactivation (fl are). Accurate diagnosis in these cases is very important fordeciding whether to start treatment or not, because acute hepatitis B does not require treatment, whilereactivation or fl are may take benefi t from it. Effort to early detect, to treat and to prevent the reactivationor fl are of chronic hepatitis B is very crucial to reduce morbidity and mortality.Keywords: Reactivation, fl are (acute exacerbation) of chronic hepatitis B, acute hepatitis B, nucleos(t)ideanalogues